2010
DOI: 10.1111/j.1547-5069.2010.01367.x
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and Obesity and Their Correlates Among Jordanian Adolescents

Abstract: Detecting the prevalence and the associated factors of overweight and obesity among adolescents is the first step toward proposing intervention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 35 publications
3
36
4
Order By: Relevance
“…Eight articles assessed BMI in relation to stress levels, and all found that higher stress was associated with higher body weight regardless of how stress was assessed (20,22,25,27,(29)(30)(31)(32). However, in three of these, significant associations were found only in female subjects (22,25,27).…”
Section: Stress and Body Weightmentioning
confidence: 87%
See 3 more Smart Citations
“…Eight articles assessed BMI in relation to stress levels, and all found that higher stress was associated with higher body weight regardless of how stress was assessed (20,22,25,27,(29)(30)(31)(32). However, in three of these, significant associations were found only in female subjects (22,25,27).…”
Section: Stress and Body Weightmentioning
confidence: 87%
“…Research conducted in Kerala, India, showed that higher position in the social hierarchy was associated with higher BMI among adults (21). Among Jordanian adolescents, higher social position was associated with lower BMI (31). Among Bosnianand Albanian-origin adolescents living in six countries, the relationship between social position and BMI differed in the two groups, with Albanians demonstrating lower body weight with higher social class and Bosnians having higher body weight with higher social class (22).…”
Section: Social Position and Body Weightmentioning
confidence: 95%
See 2 more Smart Citations
“…[22] Our results show that girls were more overweight or obese compared to boys and this has been reported in other studies from developing countries. [7,21,[23][24][25] The reverse is however the case in developed economies were boys are reportedly more overweight or obese than girls. [22,26] The explanation may be found in cultural practices that make boys do the diffi cult tasks that require physical exertion on one hand and that encourage the girls to gain weight in preparation for marriage on the other hand, in developing countries.…”
Section: Discussionmentioning
confidence: 99%